PELATIHAN PEMBUATAN BIBIT PISANG SEHAT DAN DEMPLOT PENGENDALIAN PENYAKIT DI DESA KESIUT KECAMATAN KERAMBITAN TABANAN - A.A. N. Supadma; IGN Bagus; D.M. Arthagama; I.N. Dibia (Buletin Udayana Mengabdi, 2012)
Cultivations of banana plant at dusun Kesiut Klod, desa Kesiut, Kecamatan Kerambitan, Tabanan regency were relatively non intensified. Farmers did not know plant cultivation, banana disease, and free-disease banana seedling. (free Pseudomonas solanacearum and Fusarium oxysporum). In this activity the community services aimed at transferring some information to the famers about cultivation of banana plant, fertilization for banana plant, banana diseases, and demonstration about application Biota L and Persada function for seedling banana plant. The result of this short course conducted in dusun Kesiut Klod, desa Kesiut on 26 September 2011 with 50 attendants was exciting, because most farmers were interested in the course substances and training. materials They understand and be able how to treat and apply Biota L and Persada for seedling of banana plant.